Crystallization and preliminary X-ray diffraction analysis of a novel sphingomyelinase D from Loxosceles gaucho venom - Ullah, Anwar [UNESP]; Magalhaes, Geraldo Santana; Masood, Rehana [UNESP]; Mariutti, Ricardo Barros [UNESP]; Coronado, Monika Aparecida [UNESP]; Murakami, Mario Tyago; Barbaro, Katia Cristina; Arni, Raghuvir Krishnaswamy [UNESP] (Wiley-Blackwell, 2014)
Brown spider envenomation results in dermonecrosis, intravascular coagulation, haemolysis and renal failure, mainly owing to the action of sphingomyelinases D (SMases D), which catalyze the hydrolysis of sphingomyelin to produce ceramide 1-phosphate and choline or the hydrolysis of lysophosphatidylcholine to produce lysophosphatidic acid. Here, the heterologous expression, purification, crystallization and preliminary X-ray diffraction analysis of LgRec1, a novel SMase D from Loxosceles gaucho venom, are reported. The crystals belonged to space group P2(1)2(1)2, with unit-cell parameters a = 52.98, b = 62.27, c = 84.84 angstrom and diffracted to a maximum resolution of 2.6 angstrom.